Optimalisasi Pelaksanaan Fire Drill untuk Meningkatkan Keterampilan Pemadaman Kebakaran di Kapal SPOB. Kaisar - Agung Prabowo Suleman; Albertha Lolo Tandung; Dahlia Dewi Apriani; Syamsu; Gassing (Politeknik Pelayaran Barombong, 2026)
This study aims to determine the implementation of fire drills in preventing fires on board ships and analyze the obstacles experienced by crew members in using fire drill equipment during emergencies on the SPOB. Kaisar Ship. This study uses a qualitative approach carried out on the SPOB. Kaisar Ship by collecting data through observation, interviews and documentation during the period of October 2024 to October 2025 during sailing practice activities. The results of the study indicate that fire drills are carried out routinely in accordance with SOLAS and STCW provisions, starting from briefings, fire simulations, use of APAR, fire hoses, hydrants, and fire pump inspections. The training is carried out by following a muster list so that each crew member understands their roles and responsibilities. Fire drills have been proven to improve crew skills in hazard identification, extinguisher operation, evacuation route selection, and taking rapid action in the early stages of an incident. However, the study also found several obstacles, including a lack of familiarity with some crew members' equipment, mental conditions such as panic during fire simulations, and equipment that is not always optimal or located in difficult-to-reach locations. Environmental factors such as cramped spaces, smoke, and minimal lighting also increase the challenges in utilizing safety equipment. Ineffective coordination and communication also hindered the emergency response process. Overall, the fire drills had a positive impact on improving fire preparedness and prevention on the SPOB Kaisar, but increased training, equipment maintenance, and strengthened coordination were needed to ensure maximum effectiveness in responding to emergencies. A shipboard fire drill is a systematic, periodic exercise to train the crew in handling fire situations.